2008
DOI: 10.2320/matertrans.mb200827
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation Driven Problems in Atomistic Modelling of Materials

Abstract: Understanding the mechanical properties of technologically advanced materials from quantum mechanical predictions based on electronic structure calculations remains one of the most challenging problems in modern computational materials science. In this paper, we illustrate this challenge from our current investigations on dislocation behaviour in bcc transition metals that are promising candidates for materials subject to fast neutron irradiations in future fusion power plants. Starting with the relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…As shown in figure 2, the Al x MoNbTiV HEAs have strong a metallic character due to the large positive (c 12 − c 44 ). We also observe that increasing Al content makes the value of the Cauchy pressure decrease [34] suggesting that Al reduces the metallic character of the bonding in Al x MoNbTiV HEAs.…”
Section: Cubic Elastic Constantsmentioning
confidence: 65%
“…As shown in figure 2, the Al x MoNbTiV HEAs have strong a metallic character due to the large positive (c 12 − c 44 ). We also observe that increasing Al content makes the value of the Cauchy pressure decrease [34] suggesting that Al reduces the metallic character of the bonding in Al x MoNbTiV HEAs.…”
Section: Cubic Elastic Constantsmentioning
confidence: 65%
“…Positive Cauchy pressure is featured by ductile alloys, while negative Cauchy pressure is a signature of brittle alloys. 63 The fcc structure of x ¼ 0 and the bcc structures of x ¼ 0, 0.4 and 0.8 are brittle, the rest of the structures are ductile. A z is used to predict the elastic anisotropy of materials.…”
Section: Resultsmentioning
confidence: 99%
“…Gu et al [47] reported that bulk metallic glasses with ν > 31 are very ductile. Moreover, the positive sign value of Cauchy pressure (C 11 − C 44 ) is associated with the metallic nature of polycrystalline material [48]. All three designed RHEAs show metallic nature, as all of them have a positive value of Cauchy pressure.…”
Section: Mechanical Propertiesmentioning
confidence: 95%